Islamic Communication Ethics Towards Hoax Phenomenon on Social Media - Jenuri Jenuri; Dina Mayadiana Suwarma; Muhamad Parhan; Ade Sartika; Ahmad Djubaeri Ramdani; Feby Auliya Rahmah (Dialogia: Islamic Studies and Social Journal, 2021)
The advancement of technology and information brings all goodness and convenience in this era. Although, it cannot be denied that there are also negative impacts, for example about the hoax phenomenon. So, Islamic communication on social media is very important to be applied to avoid various negative impacts caused by the hoax. This research approach was a combination of quantitative and qualitative research. Researcher used google form questionnaire to collect the data and to get more effective data, researcher collected information from journals, books, and online media to examine the ethics of student communication regarding the hoax phenomenon on social media based on Islamic perspective. The results of this research proved that tabayyun when receiving information, providing valid information to others, and maintaining words both orally and in writing are ethics that can be applied by Muslims in dealing with the hoax phenomenon.